Keefektifan Example Non Example Dalam Pembelajaran Menulis Teks Eksplanasi Siswa Kelas XI UPT SMKN 5 Pinrang - Jahara Jahara (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The implementation of the Example Non Example model in teaching explanatory text writing to the 11th grade students of UPT XI Akuntansi at SMK Negeri 5 Pinrang. This study aims to test the application of the Example Non Example model in teaching explanatory text writing to the 11th grade students of UPT XI Akuntansi at SMK Negeri 5 Pinrang. The experimental group used the Example Non Example model, while the control group used the demonstration model. This research employed an experimental method with a quantitative approach. The population of this study was all 11th grade students of UPT XI Akuntansi at SMK Negeri 5 Pinrang. The sampling technique used was probability sampling, where each element (member) of the population had an equal chance of being selected as a sample member. Data collection was conducted through a test of writing explanatory texts and questionnaire distribution. The research sample consisted of 60 students, with 31 students in class XI.1 as the experimental group and 29 students in class XI.2 as the control group. The results of data analysis using hypothesis testing through t-test calculations using SPSS version 23 showed a calculated t-value of 4.477, while the t-table value was 2.001. This indicates that the calculated t-value > t-table, which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Thus, the data analysis and hypothesis testing show a significant difference in the ability to write explanatory texts between the use of the Example Non Example model and the demonstration model. Therefore, the Example Non Example model has been proven effective in teaching explanatory text writing to the 11th grade students of the Accounting Department at UPT SMK Negeri 5 Pinrang.